Nutrition and Vitamin Deficiencies Are Common in Orthopaedic Trauma Patients - Jordan E. Handcox (MDPI AG, 2021)
Macro- and micronutrients play important roles in the biological wound-healing pathway. Although deficiencies may potentially affect orthopaedic trauma patient outcomes, data on nutritional deficiencies in orthopaedic trauma patients remain limited in the literature. The purpose of this study was to (1) evaluate the prevalence of macro- and micronutrient deficiencies in orthopaedic trauma patients with lower extremity fractures and (2) evaluate the impact of such deficiencies on surgical site complications. This retrospective study identified 867 patients with lower extremity fractures treated with surgical fixation from 2019 to 2020. Data recorded included albumin, prealbumin, protein, vitamins A/C/D, magnesium, phosphorus, transferrin and zinc, as well as wound complications. Nutritional deficiencies were found for prealbumin, albumin and transferrin at 50.5%, 23.4% and 48.5%, respectively. Furthermore, a high prevalence of micronutrient deficiencies (vitamin A, 35.4%; vitamin C, 54.4%; vitamin D, 75.4%; and zinc, 56.5%) was observed. We also recorded a statistically significant difference in wound complications in patients who were deficient in prealbumin (21.6% vs. 6.6%, p = 0.0142) and vitamin C (56.8% vs. 28.6%, p = 0.0236). Our study outlines the prevalence of nutritional deficiencies in an orthopaedic trauma population and identifies areas for possible targeted supplementation to decrease wound complications.